Faktor-Faktor Internal Individual dalam Pembuatan Keputusan Etis: Studi pada Konsultan Pajak di Kota Surabaya - Arestanti, Martana Arrazaqu; Herawati, Nurul; Rahmawati, Emi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2016)
This study aims to examine the influence of individual factors (perception of the importance of ethical and social responsibility; machiavellianism; ethical reasoning) toward ethical decision making of tax consultants. This study used 50 tax consultants as the study samples in Tax Consultant Office in Surabaya. The method of data analysis using regression analysis. This study reveals perception of the importance of ethical and social responsibility have positive influence toward ethical decision making by tax consultant, machiavellianism have negative influence toward ethical decision making by tax consultant and ethical reasoning have positive imfluence toward ethical decision making. The implication of this study is a person who has a high perception of the importance of ethical and responsibility supporting that person to conduct ethical decision making. The General Director of Taxation or the official which is delegated in issuing tax practical license needed to conduct a machiavellianism trait test from tax consultant itself. Besides, it also takes to be ensured that the tax consultant who have had the licence is an individual who has a high moral maturity (post conventional stage), so that the possibilities will be less to approve the non-ethical act and more independent in decision making which is related to ethical dilemma.